Local Aboriginal Land Councils as Environmental Managers: Practices and Opportunities - Heidi Norman (Cosmopolitan Civil Societies: An Interdisciplinary Journal, 2025)
The NSW Aboriginal Land Rights Act 1983 created a network of Local Aboriginal Land Councils (LALCs) to receive returned lands and establish Aboriginal enterprises that bolstered economic security for Aboriginal people. The restituted Aboriginal land estate has enabled Aboriginal communities to pursue ways to be back on Country, protect sites, and regenerate landscapes but their land is often overlaid with environmental and biodiversity covenants. While engaged in a larger study of the benefits of NSW Aboriginal land rights, a research team led by the author, Heidi Norman (2025), explored the ways LALCs conduct environmental management on their restituted lands, as well as public and private lands. LALCs are more than willing to care for their Country. Although they face barriers, LALCs have developed innovative environmental enterprises to carry out wide ranging work to regenerate Country and protect and care for cultural heritage and environmentally sensitive sites. This paper presents the results of a survey of LALC environmental enterprises. It discusses limitations and challenges and enabling policies that could support LALCs in NSW to expand their work.